Blowin' in the Wind – a Source of Energy: Hybrid Plasmonic and Pyroelectric Harvesting of Light Fluctuations (Advanced Optical Materials 11/2018). Issue 11 (5th June 2018) - Shiran Chaharsoughi, Mina; Tordera, Daniel; Grimoldi, Andrea; Engquist, Isak; Berggren, Magnus; Fabiano, Simone; Jonsson, Magnus P.
Abstract : In article number1701051, Magnus P. Jonsson and co‐workers present a concept for harvesting energy from light fluctuations. The concept utilizes metallic optical nanoantennas for the conversion of light fluctuations to thermal fluctuations. In turn, these thermal fluctuations are converted to electricity by an organic pyroelectric polymer. After systematic investigation of the concept, the authors demonstrate that their devices can harvest energy from light fluctuations induced by a leaf swinging in the wind.